Recién Nacido Con Diagnostico De Estenosis De Laringe - Reyes Peñafiel, Mariuxi Virginia (2018)
This pathology requires efficient knowledge and skills of both the doctor and nursing as it can lead to serious complications. This pathology is investigated in view of the need to identify and investigate its origin and its possible complications because it is frequent in neonates and pediatric patients due to the anatomy of its trachea, which requires us to provide and apply efficient knowledge and skills. It can be of congenital or acquired origin, being the most frequent acquired due to prolonged endotracheal intubation for more than 7 days, other factors are; the size of the tube used, the age of the patient, whether the procedure is performed traumatically or not, repeated intubations to maintain a patent airway, inadequate fixation of the cannula or spontaneous movements of the patient. Through the assessment by functional patterns of Marjory Gordon allowed to identify existing health problems reaching a feasible diagnosis, then to a treatment and finally to provide special nurse care for the pathology, This clinical case has as main objective to apply the process of nursing care, through care plans and interventions based on pathology, as well as the correct administration of medications, providing comfort and comfort to the patient and emotional support for family members. All Nursing Professional must have basic knowledge of this disease to understand its causes and consequences, it is important that health personnel is always prepared to intervene or help medical personnel in emergency situations.